Diffuse large B-cell lymphoma chemotherapy reveals a combined immunodeficiency syndrome in cartilage hair hypoplasia (Swiss Medical Weekly, 2018)
Cartilage hair hypoplasia (CHH) is a rare autosomal recessive ribosomopathy characterised by skeletal and integumentary system manifestations. It may also present with varied forms and intensities of haematopoietic and/or immune disorders. We report a 27-year-old female who presented a picture of combined immunodeficiency after receiving an adriamycin-based chemotherapy regimen followed by autologous stem cell transplantation. Her medical history indicated neonatal dwarfism, recurrent ear, nose and throat and respiratory infections, and hypogammaglobulinaemia, which were suggestive of a primary minor B-cell immune deficiency. Taken together, the diagnosis of cartilage hair hypoplasia was suspected and confirmed by means of molecular biological analysis. Here, we discuss the causal relationship and molecular mechanisms existing between both primary immunodeficiency and lymphoma conditions and between chemotherapy cytotoxicity and aggravation of the immune system and associated hematopoietic dysfunction, considering the role of all these components in light of the initially undiagnosed cartilage hair hypoplasia. Finally, this case highlights the importance of screening for primary immunodeficiencies in the setting of a diagnosis of lymphoma and/or dwarfism; moreover, CHH must be distinguished from other causes of small size; its diagnosis and complete check-up must include the molecular characterisation, and its management must be global in collaboration with haematologists, immunologists and internists.